From private shrine to pilgrimage centre: the spectrum of Zoroastrian shrines in Iran - Langer, Robert (Zoroastrian rituals in context, 2004)
"From Private Shrine to Pilgrim-Center: The Spectrum of Zoroastrian Shrines in Iran" published on 01 Jan 2004 by Brill.
Gesehen am 23.02.2021